Diagnosing Object-Oriented Programming Difficulties: Association Rule Mining and Block-Based Scaffolding - Andre Rangga Gintara; Lala Septem Riza; Wahyudin (Telkom University, 2026)
Logical thinking is fundamental for Object-Oriented Programming, yet vocational students frequently struggle with its abstract concepts. This study aims to overcome these cognitive barriers through a data-driven diagnostic approach and targeted intervention. Utilizing Educational Data Mining techniques, specifically Association Rule Mining, this research analyzed pretest patterns to map learning difficulties among 35 software engineering students in Indonesia. A Research and Development method with a One-Group Pretest-Posttest design was employed. The analysis revealed a